Nanoparticle transportation of CuO-H2O nanofluid in a porous semi annulus due to Lorentz forces - Sheikholeslami, M.; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal; Li, Zhixiong (Emerald Group Publishing Ltd, 2019)
Purpose The purpose of this paper is to research on CuO-water nanofluid Non-Darcy flow because of magnetic field. Porous cavity has circular heat source and filled with nanofluid. Lattice Boltzmann Method (LBM) has been used to simulate this problem. Design/methodology/approach In this research, LBM has been applied as mesoscopic approach to simulate water-based nanofluid free convection. Koo-Kleinstreuer-Li model is used to consider Brownian motion impact on nanofluid properties. Impacts of Rayleigh number, Darcy number, nanofluid volume fraction and Hartmann number on heat transfer treatment are illustrated. Findings It is found that temperature gradient decreases with rise of while it enhances with augment of Ha. Darcy number can enhance the convective flow. Originality/value The originality of this work is to analyze the to investigate magnetic field impact on water based CuO-H2O nanofluid natural convection inside a porous cavity with elliptic heat source.
Keywords: Nanofluid; Magnetic field; Free convection